Conceptual Analysis of Special Mitigating Circumstances in Romanian and European Criminal Law - Elena-Irina Rahimian (Circiumaru) (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law, 2024)
Despite the emergence of new criminal legislation and the reconfiguration of the application framework for mitigating circumstances, the scope of their applicability and the timeframe within which they may be invoked remains far from uniformly clarified at both the national and European levels. This lack of clarity persists despite numerous rulings by the Constitutional Court of Romania accepting certain exceptions of unconstitutionality or providing interpretative guidance, as well as unifying decisions on judicial practice issued by the Romanian High Court of Cassation and Justice (Î.C.C.J.) in the field under examination. Consequently, I deem it necessary to conduct an in-depth study of the special mitigating circumstances for penalty mitigation within Romanian and European criminal law, in order to contribute toward a more coherent understanding and practical application of these provisions.